Investment in infrastructure as a key to sustainable economic recovery: the role of the building industry - Ruddock, Les; Ruddock, Steven (International Journal of Strategic Property Management, 2022)
The focus of this paper is the role of the building industry in post-COVID-19 economic recovery plans. Investment in infrastructure forms a major part of many countries’ strategies to engender economic growth and construction is the pivotal industry in enabling the implementation of the plans in a sustainable manner. This study looks at the effects of investment in infrastructure on the economy with reference to the role of the construction industry in delivering this investment. Basic issues are considered, particularly concerning how relevant investment can be measured and how the contribution of the construction sector can be realistically assessed. A review of data sources and empirically peer-reviewed papers is undertaken. Based on longitudinal time series data from national statistics agencies and international organizations, analysis is undertaken to discover the relationship between infrastructure investment and economic growth. The study focuses on the UK, but comparisons are made with other countries to consider alternative approaches to stimulus investment policies with digitalization, and sustainability and green investment being a growing feature of investment plans. Potential issues of these approaches are examined and the main barriers to their achievement are identified. Emerging trends and a set of policy agendas are proposed to guide future directions.First published online 18 January 2023